2022
DOI: 10.1021/acscatal.2c04115
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Kinetic Studies of Rh(II)-Catalyzed C–H Functionalization to Achieve High Catalyst Turnover Numbers

Abstract: Detailed kinetic studies on the functionalization of unactivated hydrocarbon sp3 C–H bonds by dirhodium-catalyzed reaction of aryldiazoacetates revealed that the C–H functionalization step is rate determining. The efficiency of this step was increased by using the hydrocarbon as a solvent and using donor/acceptor carbenes with an electron-withdrawing substituent on the aryl donor group. The optimum catalyst for these reactions is the tetraphenylphthalimido derivative Rh2(R-TPPTTL)4, and a further beneficial re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 83 publications
0
9
0
Order By: Relevance
“…26 (4) Elevated temperatures enhance overall efficiency. 25 (5) Bridged tetracarboxylate ligands confer greater stability to the catalysts. 28 Using these trends as guiding principles, we conducted an optimization study for the cyclopropanation of N-Boc-2,5dihydropyrrole 9.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…26 (4) Elevated temperatures enhance overall efficiency. 25 (5) Bridged tetracarboxylate ligands confer greater stability to the catalysts. 28 Using these trends as guiding principles, we conducted an optimization study for the cyclopropanation of N-Boc-2,5dihydropyrrole 9.…”
mentioning
confidence: 99%
“…In the case of the donor/acceptor carbenes, we found that the optimum temperature for high TON was 60− 70 °C. 25,26 When the reactions with 10 were conducted at 70 °C, the yields of the cyclopropanation were still relatively low Further optimization of the Rh 2 (esp) 2 -catalyzed reaction was conducted at 90 °C, and under these conditions, the yield of exo/endo-1 greatly improved to 76% (entry 8). In the case of aryldiazoacetates, the trihaloethyl esters often gave better performance, 26 but with diazoacetates, this was not the case as the trichloroethyl derivative actually gave lower yield (entry 11).…”
mentioning
confidence: 99%
See 3 more Smart Citations